EFEKTIVITAS MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DAN REALISTIC MATHEMATICS EDUCATION TERHADAP KEMAMPUAN BERHITUNG SISWA KELAS II - Terinathe, Jullienchy Irenne; Airlanda, Gamaliel Septian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Numeracy, a fundamental skill, is often inadequately developed in students, frequently attributable to the adoption of monotonous instructional methodologies. This study aimed to evaluate and compare the effectiveness of the Contextual Teaching and Learning (CTL) model against the Realistic Mathematics Education (RME) learning model in fostering students' numeracy skills. Employing a quasi-experimental design with a Nonequivalent Control Group, the research gathered data through standardized tests, classroom observations, and supplementary documentation. The findings unequivocally demonstrate that the CTL model significantly enhances students' numeracy skills when compared to the RME model, a conclusion substantiated by robust statistical analysis. Data analysis further indicates that learning models which emphasize the inherent connection between mathematical concepts and real-life scenarios, exemplified by the CTL model, are particularly effective in cultivating numeracy. Conversely, while the RME model also incorporates real-life contexts, it was found to be less efficacious in developing critical and logical thinking processes. Based on these results, this study advocates for the adoption and implementation of Contextual Teaching and Learning (CTL) as a highly effective instructional strategy for the early development of numeracy skills, specifically within the context of mathematics education at the elementary school level.